P195 INTU: improving non-invasive ventilation (NIV) through understanding. Using patient experience to improve acute NIV provision as part of a quality improvement project. (December 2018) - Mummery, V; Matthew, D; Brown, C; Staveacre, L; Ritchie, L; McNicholas, C; Bloch, S
Abstract : Introduction and objectives: Acute NIV is an effective treatment for acute hypercapnic respiratory failure. Patients receiving acute NIV often find it distressing and poor patient experience can impact on compliance with treatment. Our aim was to understand the patient experience of NIV and use this to inform the design of our NIV quality improvement (QI) project. We aimed to develop a continuous feedback method of patient experience in order to drive the progress of the project and also to monitor the impact of changes. Method: The patient involvement strategy was developed in line with the 4Pi National Involvement Standards. Patients shared their experience through paper questionnaires, online questionnaires, structured interviews and focus groups in acute and community settings. Feedback was sought from those who had experienced NIV and those with chronic respiratory disease many of whom had little or no understanding of NIV. Relatives and carers were asked to be involved. Plan-do-study-act cycles were used when implementing changes. Thematic analysis was used to review patient experience data. Results: 101 detailed responses were received. Thematic analysis helped us to identify particular problems with the service. Table 1 shows some examples of this. Thematic analysis was used to review positive and negative responses to current service provision: we demonstrated a 33% increase in positive responses; most recent analysis showed 54% positive responses. Conclusions: By putting patients at the centre of our QI project we were able to start to make improvements that really mattered to our patients. By listening to their experience we identified key weaknesses in our service and have begun to address them. Furthermore it has enabled us to produce resources that are helpful to patients and will hopefully help to reduce the some of the anxiety surrounding NIV in hospital. By reporting the feedback in a continuous way we were able to show our staff how their efforts were resulting in improvement not only in clinical measures but also in terms of patient experience. This proved pivotal in developing the project and ensuring that our priorities were in line with those of our patients.